The Place of Irony in the Speech Portrait of a Modern Politician - Anna Aleksandrovna Gornostaeva (Russian journal of linguistics: Vestnik RUDN, 2016)
The article is devoted to the usage of irony in modern political discourse. Public speeches of modern Russian, English, and American politicians and political interviews served as material for the research. The aim of the research was to find out if irony is acceptable in political discourse and examine its influence on the speech portrait of a politician. The author's conclusion is that irony is acceptable, useful, and sometimes necessary in modern political discourse. Political debates in the modern world tend to look like talk-shows, and political information acquires the form of entertainment. This presupposes the usage of irony and humor in political discourse. Politicians use ready-made ironic utterances, as well as those created on the spot. There are also cases of unintended irony. Skillful usage of ironic mechanisms makes political speech vivid, audience-oriented, and convincing. Irony helps to put across one’s message and win the trust of the audience. This holds true for Russian as well as for English and American discourse.